Absorpcja funduszy unijnych - analiza porównawcza sytuacji finansowej gmin wiejskich woj. podlaskiego - Lasek, Mirosława; Selwesiuk, Piotr (Absorption of EU Funds - Comparative Analysis of Financial Situation for Rural Communities of the Podlaskie Voivodship, 2005)
The aim of the paper was to analyze a connection between financial situation of communities and EU funds absorption. It seems that, a communities with a better financial situation which have much money to contribute in projects co-financing from the UE budget, should apply for UE funds more often than the communities with a bad financial situation. To realize the aim the authors have compared: financial situation of communities (using the Zero Unitarization Method) and absorption of EU funds. The research covers rural communities of the Podlaskie voivodship in the years 1993-2002.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 583-592